Correlation Between Demographic Factors, Knowledge, and Motivation with Antihypertensive Medication Adherence in Patients at the Kebayoran Baru Community Health Center - Rislanniyata, Cindy Regina; Astrid, Maria (Celebes Nursing Journal, 2025)
Introduction: Hypertension is a non-communicable disease characterized by systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg and may cause serious complications in vital organs. Adherence to antihypertensive medication is a key factor in controlling this condition. Objectives: This study aimed to examine the relationship between demographic factors, knowledge, motivation, and adherence to antihypertensive medication among patients at Kebayoran Baru Community Health Center. Methods: A cross-sectional quantitative study was conducted with 64 respondents. Data were collected using the 8-item Morisky Medication Adherence Scale and analyzed with Kendall’s Tau-C and Chi-Square tests. Results: Most respondents were aged 46–80 years (81%), male (51.6%), had higher education (42.2%), and had lived with hypertension for 1–5 years (75%). Although 73.4% had high knowledge and 85.9% high motivation, medication adherence was low (60.7%). Significant associations were found between adherence and education (p = 0.001), knowledge (p = 0.041), and motivation (p = 0.046). No significant associations were found with age, gender, occupation, or duration of hypertension. Conclusion: Education, knowledge, and motivation were significantly associated with adherence to antihypertensive medication, while other demographic factors were not. Further studies should explore additional variables, such as attitudes, family support, and the role of healthcare providers, as well as develop engaging and accessible educational strategies to improve adherence.